Electrical Characteristics of Photovoltaic Cell in Solar-Powered Aircraft During Cruise - Li, Peimiao; Wang, Hui; Chang, Min; Bai, Junqiang (Frontiers in Thermal Engineering, 2022)
Aiming to study the electrical characteristics of photovoltaic cells during the flight of solar-powered unmanned aerial vehicles, this work combines a photovoltaic cell equivalent circuit model and a thermodynamic model. The influence of wing surface temperature and its influencing factor- solar radiation is of primary concern. A solar radiation model is established to explore the impact of solar irradiance on temperature and photovoltaic cell output. Atmospheric temperature and four basic parameters of photovoltaic cell, including open-circuit voltage, short-circuit current, voltage, and current at maximum power point under standard conditions are treated as input parameters. The surface temperature, the variation of output voltage, current, and power are studied with the altitude changing from 0 to 35 km and time from 0 to 24 h in spring equinoxes. Results find that with the increase in altitude, the surface temperature of the photovoltaic cell decreases first and then increases. The voltage of the photovoltaic cell decreases as the temperature increases, and the voltage-time curve varies at altitudes below 25 km and above 30 km. The peak power is available at an altitude between 15 km and 20 km. The above findings can be applied to study energy generations and flows of solar-powered vehicles.